2012
DOI: 10.1124/jpet.112.192138
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction in Neurodegenerative Diseases

Abstract: Neurodegenerative diseases are a large group of disabling disorders of the nervous system, characterized by the relative selective death of neuronal subtypes. In most cases, there is overwhelming evidence of impaired mitochondrial function as a causative factor in these diseases. More recently, evidence has emerged for impaired mitochondrial dynamics (shape, size, fission-fusion, distribution, movement etc.) in neurodegenerative diseases such as Parkinson's disease, Huntington's disease, amyotrophic lateral sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
429
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 594 publications
(457 citation statements)
references
References 101 publications
6
429
0
3
Order By: Relevance
“…These authors further suggested the presence of some common pathophysiologic features between ARSACS and some other neurodegenerative diseases with mitochondrial impairment such as Alzheimer, Parkinson, and Huntington disease. 30,31 Herein, by using TBSS, we present another common feature of ARSACS with these diseases: extensive WM alterations in the brain. 32,33 Our current study was distinguished in several ways: First, to the best of our knowledge, our study was the first that investigated whole-brain WM in patients with ARSACS.…”
Section: Discussionmentioning
confidence: 99%
“…These authors further suggested the presence of some common pathophysiologic features between ARSACS and some other neurodegenerative diseases with mitochondrial impairment such as Alzheimer, Parkinson, and Huntington disease. 30,31 Herein, by using TBSS, we present another common feature of ARSACS with these diseases: extensive WM alterations in the brain. 32,33 Our current study was distinguished in several ways: First, to the best of our knowledge, our study was the first that investigated whole-brain WM in patients with ARSACS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its central role in mitochondrial encephalopathies, mitochondrial dysfunction has been associated with various neurodegenerative CNS disorders [17], and is supposed to play important roles in the pathogenesis of WM lesioning in multiple sclerosis (MS) [7] as well in the aging brain [38]. Though the exact mechanism of vacuole formation in mitochondrial encephalopathies is not yet revealed, intramyelin WM vacuoles are presumed to develop due to intramyelin oedema secondary to mitochondrial dysfunction of oligodendrocytes, manifesting in splitting of the myelin sheath at the intraperiod line [32,40,46].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction has been implicated in neurodegenerative disorders (2), cardiovascular disease/metabolic syndrome (3), diabetes (4), and tumor development (5). Mitochondria are highly dynamic organelles that undergo fusion and fission in response to the environment and during the cell cycle, suggesting that mitochondrial dynamics and function are inter-related.…”
Section: Mitochondrial Oxidative Phosphorylation (Oxphos)mentioning
confidence: 99%